Perbandingan Dampak Lingkungan Energy Corrected Milk Produksi Susu Segar pada Peternakan Konvensional dan Peternakan Organik dengan Metode Life Cycle Assessment - Ahmad Erlan Afiuddin; Tanti Utami Dewi; Am Maisarah Disrinama; Krisna Sindu Alan Darmasaputra; Muhamad Hanif Dzulfikar (Jurnal Serambi Engineering, 2025)
KPSP Setia Kawan has two types of farms, namely conventional dairy farms and organic dairy farms. The research results show that in the milk production process of 1 kg of ECM (Energy Corrected Milk) which was delivered to the farm gate for 1 year, the total carbon footprint of milk produced by dairy farms in 2010 was 1.23 ± 0.04 kg CO2 Eq/kg ECM, 80% comes from on-farm activities. This research will apply the Life Cycle Assessment method with the CMLIA Baseline impact method. This method can be used to carry out impact assessments in the livestock sector so it is common for LCA studies in the dairy sector so it is most suitable for conducting comparative studies. It is hoped that with this research, animal husbandry can find out the effectiveness of implementing organic cattle farming in reducing environmental impacts compared to conventional cattle farming and help promote animal husbandry that prioritizes environmental aspects in the production and supporting processes.